2020
DOI: 10.3892/ol.2020.11615
|View full text |Cite
|
Sign up to set email alerts
|

PRR11 and SKA2 promote the proliferation, migration and invasion of esophageal carcinoma cells

Abstract: Proline-rich protein 11 (PRR11) together with its upstream adjacent gene, spindle and kinetochore associated 2 (SKA2), represent a classic, head-to-head gene pair. The role of the PRR11 and SKA2 gene pair has been described in various types of cancer, including breast cancer, non-small cell lung cancer, hepatocellular carcinoma and ovarian carcinoma. However, its role in esophageal carcinoma (ESCC) remains unclear. The mRNA expression levels of PRR11 and SKA2 were examined in ESCC surgical specimens. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(33 reference statements)
2
18
0
Order By: Relevance
“…Mitotic abnormalities are characteristic of most tumors ( Suzuki et al, 2018 ). PRR11 and SKA2 gene pair are overexpressed in breast cancer and esophageal carcinoma ( Chen et al, 2020 ; Wang et al, 2019 ), which accelerate proliferation, migration, and invasive capabilities. SKA2 can mediate the proliferation, migration, and invasion of breast cancer cells through EMT ( Ren et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic abnormalities are characteristic of most tumors ( Suzuki et al, 2018 ). PRR11 and SKA2 gene pair are overexpressed in breast cancer and esophageal carcinoma ( Chen et al, 2020 ; Wang et al, 2019 ), which accelerate proliferation, migration, and invasive capabilities. SKA2 can mediate the proliferation, migration, and invasion of breast cancer cells through EMT ( Ren et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of ESCC patients from the GEO database has verified the oncogenic role of PRR11 in ESCC tumorigenesis [ 29 ]. Relatively higher expression levels of PRR11 are also detected in 12 ESCC cell lines and 38 ESCC tissues than in 2 normal esophageal epithelial cells (NEECs) and the matched adjacent non-tumor tissues [ 4 , 15 ]. Further investigation revealed that PRR11 dramatically facilitated cellular proliferation and the migratory and invasive capacities of ESCC cells targeting Akt and EMT signaling via collaboration with SKA2 [ 4 ].…”
Section: Oncogenic Role Of Prr11 In Various Malignanciesmentioning
confidence: 99%
“…The PRR11 mRNA is 2408 bp in length, containing an open reading frame encoding 360 amino acids [ 2 ]. At the protein level, PRR11 is composed of a nuclear localization signal (NLS), two proline rich regions (PRs) and a zinc finger domain (ZFD) [ 4 ] ( Figure 1 a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The SKA2 expression level is upregulated in esophageal carcinoma tissues compared with the adjacent normal tissues. Through enhancing the AKT signaling pathway activity and elevating the expression of certain epithelial–mesenchymal transition-associated markers, such as N-cadherin and Snail, SKA2 could significantly participated in the regulation of esophageal carcinoma cells proliferation, migration, and invasion ( 8 ). SKA3 is a target of KIRP and predicts a poor prognosis due to its effects on the RAS/MAPK, PI3K/Akt, hormone estrogen receptor, hormone androgen receptor, DNA damage, and cell cycle ( 9 ).…”
Section: Introductionmentioning
confidence: 99%